Image Schema Verba Majemuk V1+Komu - Onin - Najmudin; Novita Puspahaty (Fakultas Komunikasi, Sastra, dan Bahasa, 2021)
This research aims to reconstructing the meaning of Japanese V1+Komu compound verbs through images schema theory. The data gathered from The Compound Verb Lexicon (NINJAL, 2015). Based on analysis through image schema, the verb –komu as a second verb (V2) add meaning ‘go in/into’ space or place. These meaning are: (a) go in/into three-dimensional space; (b) go in/into two-dimensional space; (c) go in/into one-dimensional space; (d) go in/into space or place because of gravity law; (e) covering; (f) permeating into something; (g) go in/into something by suctioning